Application of Rosemary and Eucalyptus Essential Oils and Their Main Component on the Preservation of Apple and Pear Fruits - Panayiota Xylia (MDPI AG, 2021)
Nowadays, increase fruit losses are being reported due to the development of fungal postharvest diseases. In an attempt to reduce the use of synthetic fungicides, a turn towards natural products such as essential oils (EOs) and natural compounds has been made. The objective of this study was to investigate the effects of eucalyptus (Euc), rosemary (Ros) EO, their mixture (50:50 v/v) and their common main component (i.e., eucalyptol) on the quality parameters, fruit response and inhibition of blue rot (Penicillium expansum) in apple and pear fruits during their shelf life. The results of the present study revealed that fungal colony growth decreased in vitro with exposure at eucalyptus EO (Euc-300 μL/L), rosemary EO (Ros-300 μL/L) and their mixture (Euc + Ros 100 and 300 μL/L). The exposure at Ros-100 μL/L stimulated spore production, whilst Euc + Ros (100 and 300 μL/L) and eucalyptol (100 and 300 μL/L) decreased spore germination. Moreover, the in vivo applied treatments resulted in decreased lesion growth of P. expansum in apple and pear fruits. Respiration rate increased with the application of Euc + Ros at 300 μL/L and eucalyptus EO (Euc-100 μL/L and Euc-300 μL/L) for both assessed fruits. On the other hand, no significant differences were reported on apples and pears total soluble solids and acidity values. The application of Euc + Ros-300 μL/L in apples increased hydrogen peroxide (H2O2) levels, whilst Euc-100 and Euc-300 μL/L increased lipid peroxidation levels. Regarding pear fruits, exposure to Euc-100 μL/L and Ros-100 μL/L resulted in increased H2O2 whereas, Euc-100 μL/L, Ros- (100 and 300 μL/L) and eucalyptol (100 and 300 μL/L) also increased lipid peroxidation. The findings of this study indicate that the investigated natural products can be explored for the preservation of fresh apples and pears, as alternative natural fungicides with consideration of the fresh produce quality attributes.